Tradução e localização de software e outros produtos: Audiovisual ou Multimídia? - Gabriela Castelo Branco Ribeiro (Cadernos de Tradução, 2005)
This paper presents the localization process of software and other multimidia products based on my experience as a localizer, and considering its translational, technological, market-driven, cultural and audiovisual aspects. In order to do so, we discuss the main peculiarities of localization regarding technological variety, translation tools, working and training conditions, and linguistic requirements, which represent opportunities and challenges to professionals in the area. Traditionally, this process is presented from a market viewpoint, taking translation as one of its steps only. The present work, however, aims at reviewing this approach by suggesting points of intersection between localization and translation studies, with special emphasis to audiovisual aspects. Keywords: localization, multimidia, audiovisual translation, translation tools.